Evaluation Analysis Study of the Integration of Islamic Values in Sociology Learning in Fostering Islamic Character - Tatang Hidayat; Ahmad Syamsu Rizal; Aam Abdussalam; Aceng Kosasih; Istianah (Faculty of Social Science, Universitas Negeri Malang, 2024)
The discovery of a dichotomy between general science and religious science both in terms oftheory and practice in the implementation of learning at the elementary / junior high school / highschool / equivalent and university levels in Indonesia causes various problems. The purpose ofthis study is to find a hypothetical model of evaluating the integration of Islamic values in sociologylearning in fostering Islamic character at SMA PGII 2 Bandung. This research uses a qualitativeapproach and descriptive method of case study types. The researcher acts as the maininstrument. Data retrieval techniques with interviews, observations, and documentation studies.Data analysis techniques with data reduction, data coding, data display, interpretation of findingsand drawing conclusions. Test the credibility of the data by extending the research time,increasing perseverance, triangulating data, using reference materials and focus groupdiscussions. Based on the results of the study, the evaluation of the integration of Islamic valuesin sociology learning at SMA PGII 2 Bandung has not occurred comprehensively. The evaluationin sociology learning has been systematically planned. Aspects evaluated as well as planning inlearning tools include aspects of attitudes, knowledge, and skills. The attitude evaluationinstrument in sociology learning is almost the same as schools in general, namely using anattitude evaluation instrument based on the 2013 curriculum. However, in its implementation, theemphasis on evaluation is still dominant in the aspect of knowledge. The development of socialattitudes and skills of students after participating in sociology learning integrated with Islamicvalues has not been felt thoroughly, because the attitudes assessed have not been integratedwith ilāhiah values. On the other hand, the written evaluation of the integration of Islamic valuesin sociology learning at the level of material substance has not been integrated, because theteacher only evaluates the material as it is in the package book.